2019
DOI: 10.1002/pbc.27786
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of proton therapy in children with high‐risk and locally recurrent neuroblastoma

Abstract: Purpose Proton therapy is currently used in the management of pediatric tumors to decrease late toxicities. However, one of the criticisms of proton therapy is the limited data regarding efficacy on disease control. The purpose of this study was to examine local and distant control rates after proton therapy for neuroblastoma. Methods and materials Eighteen patients with high‐risk (n = 16) and locally recurrent neuroblastoma (n = 2) were treated with curative intent and received proton therapy to the primary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Our study complements the existing literature on children undergoing RT for NB confirming high LC and acceptable OS. Local control and survival rates were similar to other studies, which demonstrated a 3- to 5-year LC and OS of 64.7–97% and 35–94% ( 13 , 19 27 ). In the literature, the most common late effects associated with RT were musculoskeletal abnormalities, gastrointestinal dysfunctions, metabolic disorders, vascular changes, and secondary malignancies ( 22 , 28 31 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study complements the existing literature on children undergoing RT for NB confirming high LC and acceptable OS. Local control and survival rates were similar to other studies, which demonstrated a 3- to 5-year LC and OS of 64.7–97% and 35–94% ( 13 , 19 27 ). In the literature, the most common late effects associated with RT were musculoskeletal abnormalities, gastrointestinal dysfunctions, metabolic disorders, vascular changes, and secondary malignancies ( 22 , 28 31 ).…”
Section: Discussionsupporting
confidence: 88%
“…Planning studies in NB have shown that PBT can considerably reduce the radiation exposure of adjacent healthy tissue, potentially reducing the radiation-induced toxicities ( 11 , 12 ). Furthermore, there are already clinical data demonstrating the effectiveness and feasibility of PBT for NB patients ( 13 , 14 ). The current study reports on our experiences when treating patients with NB with special consideration of PBT in an intensive multimodal therapy concept.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, 40% of NB patients suffer from high-risk disease which is easy to relapse and lethal (1,4). Various kinds of therapeutic methods have been adopted to treat high-risk NB, including surgical treatment, chemotherapy, radiotherapy, immunotherapy, cis-retinoic acid, and proton therapy (5), but the prognosis of NB is still poor due to the complex mechanisms underlying NB occurrence and development. Therefore, it is urgent to further reveal the molecular mechanisms of NB in order to find novel and potent targets for the treatment of NB.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with neuroblastoma can be classified into three risk groups: low risk, intermediate risk and high risk by using some clinical and biological prognostic factors. Patients with a non‐high risk (low and intermediate risk) of neuroblastoma have a long‐term survival rate up to of 90% or above, while those with high risk of neuroblastoma only achieve a survival rate as low as 40% …”
Section: Introductionmentioning
confidence: 99%
“…Patients with a non-high risk (low and intermediate risk) of neuroblastoma have a long-term survival rate up to of 90% or above, while those with high risk of neuroblastoma only achieve a survival rate as low as 40%. 10,11 In recent decades, remarkable advancement has been achieved in comprehending the fundamental aetiology of neuroblastoma. 12,13 Children's and pregnant women's exposures to many environmental factors were reported to predispose to neuroblastoma, yet the causality could not be finally confirmed.…”
Section: Introductionmentioning
confidence: 99%